PENERJEMAHAN REGISTER MILITER PADA SUBTITLING FILM â€THE GREAT RAIDâ€ - Ardi, Havid (English Department FBS UNP, 2013)
Subtitling is a kind of audiovisual translation/AVT. Translating oral dialogue into text (subtitling) has various aspects that must be considered, such as time exposure, space limitation. Related to sociolinguistic aspect, it is also known that language user and usage determined by various factor such as age, sex, and profession. One of the objects in sociolinguistics is register, a language variation, that exist in any social group. This research is aimed at discovering the ways of subtitler translating military register as the character of a social group. The tentative finding shows that military register tends to be translated in general term. Â Keyword: subtitling, military register, audiovisual translation